Acute polyneuropathy: a serious complication of levodopa/ /carbidopa intestinal gel treatment for Parkinson's Disease - Havránková, Petra; Roth, Jan; Čapek, Václav; Klempíř, Jiří; Baláž, Marek; Rektorová, Irena; Haň, Vladimír; Skorvanek, Matej; Gmitterová, Karin; Minár, Michal; Valkovič, Peter; Kaiserová, Michaela; et al. (Neurologia i neurochirurgia polska, 2024)
AIM OF STUDY: To determine whether a high dose of levodopa-carbidopa intestinal gel (LCIG), expressed as levodopa equivalent daily dose (LE daily dose), is a risk factor for acute polyneuropathy in patients treated with LCIG. CLINICAL RATIONALE FOR STUDY: Treatment with LCIG is an effective device-assisted therapy in the advanced stages of Parkinson's Disease (PD). Polyneuropathy is a well-known complication of PD treatment. Patients treated with oral levodopa usually suffer from sub-clinical or mild chronic sensory polyneuropathy. However, severe acute polyneuropathy occurs in patients treated with LCIG, which is causally related to the treatment and leads to its immediate discontinuation. The etiology is not yet clear, but some patients with acute polyneuropathy have been given high doses of LCIG. MATERIAL AND METHODS: A retrospective multicentre study of patients treated with LCIG was performed. Patients with acute polyneuropathy were subjected to a detailed analysis including statistical processing. RESULTS: Of 183 patients treated with LCIG in seven centres, six patients (five females, median age 63 years) developed acute polyneuropathy with LCIG discontinuation. The median (interquartile range) initial and final LE daily dose in patients with and without acute polyneuropathy was 3,015 (2,695-3,184) and 1,898 (1,484-2,167) mg, respectively. The final LE daily dose of 2,605 mg cut-off had 83% sensitivity and 93% specificity for the prediction of acute polyneuropathy. CONCLUSIONS AND CLINICAL IMPLICATIONS: The risk of acute polyneuropathy in LCIG-treated patients was associated with a daily LE dose of greater than 2,605 mg or with more than a 62% increase in the daily LE dose during LCIG treatment.
Keywords: mužské pohlaví; Retrospective Studies; Drug Combinations; Parkinsonova nemoc; Male; Gels; senioři; retrospektivní studie; Female; Humans; Parkinson’s Disease; lidé; Middle Aged; ženské pohlaví; lidé středního věku; levodopa/carbidopa intestinal gel; acute polyneuropathy; Antiparkinson Agents; Levodopa; Parkinson Disease; levodopa; gely; levodopa equivalent daily dose; polyneuropatie; karbidopa; Carbidopa; antiparkinsonika; Aged; Polyneuropathies; fixní kombinace léků